Quality of stock markets - Loh, Aizhen (2008)
This paper examines the stock market qualities in Hong Kong, Malaysia, Singapore, Taiwan and Thailand over a ten-year period. We explore a new arena of research as many early academics who investigated on market quality largely focused on comparisons between countries or factors such as liquidity, volatility and transaction costs.